Tingkat Penguasaan Kosakata Bidang Lingkungan oleh Siswa tingkat SMP - Sylvi Tri Andani; Dewi Anggraini (Jurnal Bahasa dan Sastra, 2023)
Adequate vocabulary mastery, especially in the environmental field, is the basic capital for students to be able to express their ideas well, especially those with environmental themes. Based on this, this research is motivated by the phenomenon of vocabulary mastery in the field of student environment which is relatively minimal. The purpose of this study was to describe the level of vocabulary mastery in the environment field for Grade VIII students of junior high school. This type of this research is quantitative research using descriptive methods. Quantitative analysis is used to measure and describe the level of environmental vocabulary mastery of students. The population in this study were all class VIII students of SMP Negeri 6 Kubung for the academic year 2022/2023 with a total of 22 students. The sample in this study amounted to 22 students using the total sampling technique. Data collection was carried out through a vocabulary mastery test in the environmental field. Based on the acquisition and processing of research data, the results obtained were that the level of environmental vocabulary mastery of class VIII students of SMP Negeri 6 Kubung was in the range of 66-75 on a scale of 10 with a score of 74.03. Based on the results of this study it was concluded that in terms of vocabulary mastery in the field of environment students were at more than sufficient qualifications.